Correct and Timely Referral of Patients to Centers of Reference - Costa, Joana; Valença-Filipe, Rita; Rodrigues, Jorge (Acta Médica Portuguesa, 2013)
The correct and timely referral of patients, from peripheral hospitals, without specialized surgical care, namely in hand surgery, like Plastic Surgery or Orthopedics is of crucial importance. The authors report the case of a patient that presents in the Plastic Surgery Department with a chronic infection of the hypothenar eminence of the right hand. The clinical history suggests the persistence of a foreign body, despite two previous surgical procedures for removal, performed in the residence hospital. Surgical exploration was performed and the foreign body was removed without complications. The intent of this presentation is to alert for the importance of the timely referral of patients that can benefit of specialized care, namely of plastic surgery, when this is no possible in the residence hospital, in view of better health care and better patient treatment.